Degradation of Solanum xanthocarpum Leaves Protein - A. Pawar, Ashwini; S. Goswami-Giri*, Anita (Asian Journal of Chemistry, 2011)
Inside plant cells, the enzyme ribulose bisphosphate carboxylase/oxygenase (rubisco) forms the bridge between life and the lifeless, creating organic carbon from the inorganic carbon dioxide in the air. But only three carbon dioxide molecules are fixed by rubisco per second. Chloroplasts are filled with rubisco, which comprises half of the protein which contributes upto 50 % soluble protein and 30 % of total leaf nitrogen in leaves of C3 plants. This makes rubisco the most plentiful single enzyme on the earth. In the present study, Solanum xanthocarpum leaves protein and carbohydate contents was 12 and 18 %, respectively. It was used for the degradation and the neutralization of it for the nitrogen composition in the environment. Protein degradation considerd when 1 mM SDS and EDTA used under different stress conditions. Protein degradation limits at 60 ºC using tris buffer pH 8.0 at 1 h with stirring. Characterization and degree of dissociation of rubisco/protein was determined by splitting property of bands on gel electrophoresis and discrete spots on TLC.